2012
DOI: 10.1007/s10195-012-0183-1
|View full text |Cite
|
Sign up to set email alerts
|

Failure of intertrochanteric nailing due to distal nail jamming

Abstract: Nail impingement against the anterior femoral cortex during nail insertion, or anterior cortex penetration, has been described in the literature as a worrying complication. We describe a previously unreported surgical failure due to a compromised dynamic distal locking caused by distal jamming of the nail. An 80-year-old male suffered a closed right intertrochanteric femoral fracture. Due to the presence of a long medial fragment, a 240 mm long titanium trochanteric nail was chosen to stabilize the fracture. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The risk of distal shaft fractures was not associated with the patient age, gender, fracture type, or cortical bone index [ 13 23 ]. Maniscalco et al presented a rare case of 31-A2 nonunion and breakage of an EndoViS® nail (Citieffe™, Calderara di Reno, Bologna, Italy), due to failure at the hole for the dynamic locking screw, caused by distal jamming of the tip of the nail against the anterior cortex [ 24 ]. A surgical failure due to distal jamming had never been described in the literature before [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of distal shaft fractures was not associated with the patient age, gender, fracture type, or cortical bone index [ 13 23 ]. Maniscalco et al presented a rare case of 31-A2 nonunion and breakage of an EndoViS® nail (Citieffe™, Calderara di Reno, Bologna, Italy), due to failure at the hole for the dynamic locking screw, caused by distal jamming of the tip of the nail against the anterior cortex [ 24 ]. A surgical failure due to distal jamming had never been described in the literature before [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maniscalco et al presented a rare case of 31-A2 nonunion and breakage of an EndoViS® nail (Citieffe™, Calderara di Reno, Bologna, Italy), due to failure at the hole for the dynamic locking screw, caused by distal jamming of the tip of the nail against the anterior cortex [ 24 ]. A surgical failure due to distal jamming had never been described in the literature before [ 24 ]. Liu et al in a retrospective review of 341 intertrochanteric fractures treated with the TFN found two patients whose nails had failed at the junction of the helical blade and the nail.…”
Section: Discussionmentioning
confidence: 99%
“…Intramedullary fixation device has advantages from the biomechanical point of view and has become increasingly popular in treating unstable trochanteric fractures [1, 2], but serious implant-related complications have been reported, such as femoral shaft fracture [3], cutting out [4], lateral migration of the femoral neck screw [4, 5], and distal locking [6, 7]. In 2003, the AO/ASIF group developed the Proximal Femoral Nail Antirotation (PFNA) to improve the rotational and angular stability with a helical blade which can avoid bone loss that occurs during the drilling and insertion of a standard sliding hip screw [8].…”
Section: Introductionmentioning
confidence: 99%
“… 49 Anterior impingement has also been described in locked nails and although theoretically may be associated with nonunion and peri-implant fractures, it has not yet been proven. 50 , 51 , 52 …”
Section: Resultsmentioning
confidence: 99%
“… 38 Additional unstable fracture patterns that benefit from locked nailing include fractures with an incompetent lateral wall, severe dorsomedial comminution, subtrochanteric extension and a wide intramedullary canal. 6 , 52 , 54 …”
Section: Discussionmentioning
confidence: 99%